Detection of pulmonary embolism with free‐breathing dynamic contrast‐enhanced MRI. Issue 4 (22nd September 2015) - Ingrisch, Michael; Maxien, Daniel; Meinel, Felix G.; Reiser, Maximilian F.; Nikolaou, Konstantin; Dietrich, Olaf
Abstract : Purpose: To evaluate the use of dynamic contrast‐enhanced (DCE) magnetic resonance imaging (MRI) during free breathing for the detection of acute pulmonary embolism (PE). Materials and Methods: Eighteen subjects underwent free‐breathing DCE MRI at 1.5T, eight of whom were patients with acute PE, as confirmed by routine computed tomography pulmonary angiography (CTPA). The remaining 10 subjects were healthy volunteers with no history or signs of pulmonary disease. From all DCE MRI data, maps of relative signal enhancement were calculated and assessed for the presence or absence of perfusion defects in each lung by two readers. Interreader variability, sensitivity, and specificity of free‐breathing DCE MRI for the detection of PE were calculated using CTPA as the gold standard. Results: Of the 16 patient's lungs, 15 were affected by acute PE according to CTPA. In patients and volunteers, DCE MRI sensitivity was 93% and 87% for readers 1 and 2, with specificities of 95% and 90%, respectively. Interreader agreement was substantial, with κ = 0.77 (95% confidence interval: 0.44–1.0). Conclusion: Free‐breathing DCE MRI may have potential use for the assessment of PE, and does not require patient cooperation in breath‐holding J. Magn. Reson. Imaging 2016;43:887–893